The Serat Samud Within and Beyond Javanese Palace Circles - Ronit Ricci (Masyarakat Pernaskahan Nusantara (The Indonesian Association for Nusantara Manuscripts, Manassa), 2017)
This paper discusses about Javanese text Serat Samud or Suluk Samud. The story tells about Jewish scholar, Samud Ibnu Salam who make some dialogues with prophet Muhammad. It was translated from Arabic into Javanese since 17c. There are many versions in archipelago, include Malay, Bugis, Arabic and Makassar. If its compared with another textual traditions, and this can be understood as evidence that Serat Samud indeed is considered important by the community of Java in the past. The text copied and read in the Javanese court, including the Palace of Surakarta and Pakualaman duchy. From the other side, its clear that the text copied outside palace, like in village and pesantren. This paper will formulate our ideas about presence or absence of boundaries between inside and outside of the palace of Java in the eighteenth and nineteenth centuries. — Artikel ini membicarakan teks Jawa yang berjudul Serat Samud atau Suluk Samud. Cerita teks ini mengenai seorang pandhita Yahudi bernama Samud Ibnu Salam yang berdialog dengan Nabi Muhammad. Cerita ini diterjemahkan ke dalam bahasa Jawa sekitar abad ke-17, kiranya dari bahasa Arab. Di Nusantara terdapat banyak versi, termasuk dalam bahasa Melayu, Bugis, Arab dan Makassar, dan ini bisa dipahami sebagai bukti bahwa Serat Samud memang dianggap penting oleh masyarakat Jawa di masa lampau. Serat Samud disalin dan dibaca di lingkungan istana Jawa, termasuk Keraton Surakarta and Kadipaten Pakualaman. Dari sisi lain, jelas juga bahwa banyak naskah Serat Samud disalin di luar keraton dan istana, di desa dan di pesantren. Tulisan ini merumuskan ide-ide kita mengenai ada tidaknya semacam batasan antara keraton dan non-keraton di Jawa selama abad kedelapan dan kesembilan belas.